The costly call : modern-day stories of Muslims who found Jesus - Caner, Emir Fethi; Pruitt, H. Edward (Grand Rapids, MI : Kregel Publications, 2005)
"Personal narratives of the consequences of converting to Christianity from Muslims around the world"--Provided by publisher.
Keywords: Christian converts from Islam